Pulling together : a guide for teachers and instructors - Allan, Bruce; Biin, Dianne; Chenoweth, John; Hardman, Shirley Anne; Hobenshield, Sharon; Lacerte, Louise; Ormiston, Todd; Perreault, Amy; Wilson, Justin; Wright, Lucas; BC Open Textbook Project (BCcampus, BC Open Textbook Project, 2018)
"A Guide for Teachers and Instructors is part of an open professional learning series developed for staff across post-secondary institutions in British Columbia. These guides are the result of the Indigenization Project, a collaboration between BCcampus and the Ministry of Advanced Education, Skills and Training. The project was supported by a steering committee of Indigenous education leaders from BC universities, colleges, and institutes, the First Nations Education Steering Committee, the Indigenous Adult and Higher Learning Association, and Métis Nation BC. These guides are intended to support the systemic change occurring across post-secondary institutions through Indigenization, decolonization, and reconciliation."--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Includes bibliographical references.
Description based on online resource; title from HTML title page (viewed on September 19, 2018).
Keywords: Native peoples -- Education -- Canada -- Textbooks; Indigenous peoples -- Education -- Canada -- Textbooks; Electronic books